Indigenous Counseling Service Process at Bani Sholeh An Nawawi Islamic Boarding School - Afrizal Rizki; Azat Sudrajat; Aulia Nur Nabillah; Indah Fitriyani; Agus Sukirno (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the process of indigenous counseling services in Pondok Pesantren Bani Sholeh An Nawawi. The background of this research is the complexity of students’ problems in Islamic boarding schools, especially in salaf pesantren, which require an approach based on religious and cultural values. The purpose of this study is to analyze the stages of problem handling, forms of services, and the values underlying the counseling process. This research uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation. The results show that indigenous counseling in pesantren is carried out collectively through a hierarchical system involving student leaders, caretakers, and parents.